ENSURING ECO-ORIENTED VOCATIONAL TRAINING OF FUTURE QUALIFIED WORKERS (Innovative professional education, 2023)
The article deals with the problem of ensuring eco-oriented vocational training of future qualified workers. The forms of оrganization of the educational process are revealed. Modern approaches to the formation of environmental competence of future specialists are substantiated.
Keywords: ecological competence, «green» professions, energy efficiency, teachers on special subjects, ecological projects